Kpop Fans Fanatism In Social Media Instagram - Wahdah Annisa Amri (Pena Cendekia Insani, 2020)
This study aims to determine the fanaticism of K-pop fans onInstagram and to find out how K-pop fans respond to hoaxes andnegative information about their idols. This study uses a qualitativedescriptive method with data collection techniques interview andliterature study. Informants were selected using purposive samplingtechnique. The results show that fan fanaticism on Instagram can beseen through fan activities such as making meanings, various meaningsin the form of interpreting K-pop idol posts as motivation to work,making posts of admiration and pride for their K-pop idols. Hunt byfollowing fansite accounts and making fan fiction and videos. Collectand upload pictures of their official K-pop merchandise and buildknowledge between fans. K-pop is also expressed through fanresponses to hoaxes and negative information from their idols. Theresponse is influenced by the age of fans, knowledge of K-pop culture,environment, time as a K-pop fan. In seeking clarification about thetruth of the negative news, they look for trusted sources such as K-popidols' official Instagram accounts, official Instagram accountmanagement management, major Korean media such as Soompi,Allkpop, and press releases provided by artist management.